2021
DOI: 10.1111/1751-2980.13048
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection versus endoscopic mucosal resection for rectal carcinoid tumor. A meta‐analysis and meta‐regression with single‐arm analysis

Abstract: Objective As there has been so far no consensus on the best endoscopic resection technique, a meta‐analysis was conducted to compare the efficacy and safety of endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR) for treating rectal carcinoid tumors. Methods MEDLINE and EMBASE databases were searched for articles on the treatment of rectal carcinoid tumors using ESD vs EMR published up to October 2020 for outcomes including en bloc and complete resection, margin involvement, procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
0
10
0
2
Order By: Relevance
“…However, ESD has the disadvantage that the technique is difficult to learn, the procedure time is long, and the risks of bleeding and perforation are higher than those of m-EMR. 27 , 29 , 40 , 43 , 45 , 46 Yong et al 41 reported a perforation rate of 2% and a bleeding rate of 7%. Incomplete resection and complications may occur if ESD is performed by an inexperienced operator.…”
Section: Which Methods Is Best?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, ESD has the disadvantage that the technique is difficult to learn, the procedure time is long, and the risks of bleeding and perforation are higher than those of m-EMR. 27 , 29 , 40 , 43 , 45 , 46 Yong et al 41 reported a perforation rate of 2% and a bleeding rate of 7%. Incomplete resection and complications may occur if ESD is performed by an inexperienced operator.…”
Section: Which Methods Is Best?mentioning
confidence: 99%
“…Nevertheless, ESD is required if the lesion is too large, suctioning is not possible due to fibrosis in the lesion, or if the snaring for EMR does not work well. In a meta-analysis including 1,360 lesions, Yong et al 41 reported that ESD for rectal NETs >10 mm demonstrated a higher complete resection rate and lower vertical margin involvement than EMR.…”
Section: Which Methods Is Best?mentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal well-differentiated NETs smaller than 2 cm can be treated with endoscopic resection considering their very low metastatic potential and the tendency to be confined in the mucosa/submucosa. Tumors larger than 2 cm or those localized in other sites of the colon need to be treated with surgical excision similarly to adenocarcinomas [ 45 ]. The medical treatment of poly-metastatic disease overlaps with that of other gastrointestinal high-grade NETs [ 42 ].…”
Section: Rare Tumors Of Colon and Rectummentioning
confidence: 99%
“…Die konventionell durchgeführte EMR (mit/ohne submukösem Flüssigkeitskissen) zeigte sich in vielen Studien immer wieder den modifizierten EMR-Techniken (Kappen-EMR, EMR nach Gummibandligatur, EMR nach zirkumferenzieller Inzision) und auch der ESD in Bezug auf die komplette Resektionsrate unterlegen [34,35,36], sodass sie beim Verdacht auf das Vorliegen eines NET keine Anwendung finden sollte. In allermeist retrospektiven Arbeiten konnten für die modifizierte EMR sowie die ESD absolut vergleichbare histologische R0-Resektionsraten von ≥ 90 % gezeigt werden, wobei das Risiko von Komplikationen niedrig war [36,37,38,39]. Eine endoskopische Alternative kann auch die Over-the-Scope-Vollwandresektion (FTRD "full thickness resection device") sein [40].…”
Section: Rektum-netunclassified